Nilai-Nilai Pendidikan Karakter dalam Kitab Syi’ir Ngudi Susila dan Mitra Sejati - Arif Muzayin Shofwan; Miftakhul Rohman (CENDEKIA, 2022)
There are various ways to build character in early education institutions. One of the methods used at Madrasah Diniah Miftahul Huda Sekardangan Blitar is through the Book of Syi'ir Ngudi Susila and the Book of Syi'ir Mitra Sejati. This literature study aims to examine the values ​​of character education in the two books. This descriptive-qualitative writing reveals the character education values ​​of the two books. First, the values ​​of character education in the Book of Syi'ir Ngudi Susila are related to the following matters, including manners of children to their parents, the discipline of time, manners related to school, manners of students at home, manners of children towards teachers. , children's manners when parents receive guests, as well as vigilance and keeping traditions. Second, the values ​​of character education in the Book of Syi'ir Mitra Sejati relate to the following matters, including humanity, the manners of children towards their fathers, the manners of children towards their mothers, the manners of the people to the government, the manners of students towards their parents. teachers, manners towards fellow friends, careful attention, manners in speaking, etiquette in dealing with others, maintaining health, eating manners, dress manners, keeping the house and room clean, adult obligations, frugal, visiting others and receiving guests, visiting the sick, mourning the dead, and etiquette for wedding invitations.